2003
DOI: 10.1097/01.psy.0000058377.50240.64
|View full text |Cite
|
Sign up to set email alerts
|

Test of an Interpersonal Model of Hypochondriasis

Abstract: The findings indicate that hypochondriacal patients are insecurely attached and have interpersonal problems that extend to and include the patient-physician relationship. These data support the proposed interpersonal model of hypochondriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
87
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 43 publications
11
87
0
Order By: Relevance
“…Studies have shown neuroticism to be strongly positively associated with health anxiety (McClure & Lilienfeld, 2001;Noyes et al, 1994;. In interpersonal models of health anxiety, neuroticism has been shown to be a predictor of health anxiety and strongly associated with attachment styles (Noyes, 2003). Some authors have proposed that health anxiety may just be a manifestation of neuroticism (Watson, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Studies have shown neuroticism to be strongly positively associated with health anxiety (McClure & Lilienfeld, 2001;Noyes et al, 1994;. In interpersonal models of health anxiety, neuroticism has been shown to be a predictor of health anxiety and strongly associated with attachment styles (Noyes, 2003). Some authors have proposed that health anxiety may just be a manifestation of neuroticism (Watson, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In a large (n ϭ 701) sample of female primary care patients in a health maintenance organization, Ciechanowski and colleagues (14) found that patients with insecure attachment styles reported a significantly greater number of physical symptoms than those with a secure attachment style, and the strongest association was between fearful attachment style and greater symptom reporting. Similarly, Noyes and colleagues (11) found that insecure attachment, especially fearful attachment, was associated with greater symptom reporting in a sample of 162 patients in a general medical clinic. A critical question is whether attachment style might help explain the associations found previously between childhood trauma and adult somatic symptoms.…”
Section: Attachment and Somatizationmentioning
confidence: 99%
“…Bowlby (10) first proposed the idea that repeated interactions between infants and their caregivers prompt infants to develop models of both seeking and receiving care from those on whom they depend. These models, or attachment styles, tend to persist throughout life and influence the expectations that people bring to their dealings with others, particularly to their dealings with those they might depend on for needed support or advice such as family members, romantic partners, and physicians (11). Bartholomew and Horowitz (12) empirically validated a classification system of one secure and three insecure adult attachment styles.…”
Section: Attachment and Somatizationmentioning
confidence: 99%
“…The main disorder accompanying health anxiety is hypochondriasis, but this also commonly occurs in other somatic symptom disorders. 10 The aim of the present study was to investigate health anxiety and depressive symptoms in patients with FMS, and also to explore whether any relationships exist among health anxiety and disease activity scores (FIQ), pain levels (VAS) and depression scales.…”
Section: Introductionmentioning
confidence: 99%